-6(-2x-4)=-3(-4x-8)

Simple and best practice solution for -6(-2x-4)=-3(-4x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-2x-4)=-3(-4x-8) equation:



-6(-2x-4)=-3(-4x-8)
We move all terms to the left:
-6(-2x-4)-(-3(-4x-8))=0
We multiply parentheses
12x-(-3(-4x-8))+24=0
We calculate terms in parentheses: -(-3(-4x-8)), so:
-3(-4x-8)
We multiply parentheses
12x+24
Back to the equation:
-(12x+24)
We get rid of parentheses
12x-12x-24+24=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2x-16.5=4x+7.5 | | 339.12=18.84j | | 3c-32=2c-14 | | 3(2)=6b+18b | | 14+u/2=20 | | -1+k/8=1 | | 7c-12=56 | | 9-1.50m=21.000 | | 3x+9=3x–8 | | 2(v+8)+-9=-5 | | 6t-31=5t-22 | | 7(b+10)=84 | | 1/2x-6=(-6)+1/2x | | 2(a+1)=a+4 | | 2(4x+1)=3x+3+4 | | 0.8(q+-14)+-12.1=-11.3 | | 23x=5x^2+34 | | 11x-8=14x+7 | | 3|2x+8|=36 | | (x-0.2x)^3=0 | | 3p+24=33 | | 9h-1.50=21.000 | | 15x+4=13x+8 | | -0.9-0.2y=0.5 | | 21x+8x+14x=214 | | -6u+4(u-5)=-26 | | -3(x-4)=4 | | 23,665x=0,0000255x^2+341590 | | 8x+3+10x-15=180 | | 10s=15+15-10 | | 0.5x^2+5x+7=0 | | 12(2x+2)-5x=5x-6(x-4) |

Equations solver categories